Seed priming by sodium nitroprusside improves salt tolerance in wheat (Triticum aestivum L.) by enhancing physiological and biochemical parameters - Ali, Qasim (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017. Published by Elsevier Masson SAS.